Fundamentals of metal cutting : textbook - Moshchenok, Vasyl; Pimonov, Igor; Chevychelova, Olena (LAMBERT Academic Publishing, 2025)
The textbook covers various aspects of metalworking by cutting, starting with the physical fundamentals and characteristic types of movements in metal cutting machines and focusing on the geometrical parameters of cutting tools. It covers the mechanism of chip formation and build-up in detail, explains the nature of the cutting forces involved, and analyses the thermal phenomena that occur during operation. A separate section is devoted to cutting tool life and wear. The book covers a variety of tool materials, including carbon steels, alloy steels, high-speed steels, hard alloys, and superhard materials. The design of various cutting tools such as cutters, drills, milling cutters, broaches, broaches and gear cutting tools is described in detail, with an emphasis on determining cutting conditions. Particular attention is paid to the classification and marking of metal-cutting machines, including turning, drilling, milling, grinding, broaching, and other machines with numerical control systems. The publication contains control questions, tasks for independent work and tests to help students and professionals consolidate their knowledge.
Keywords: mechanical engineering; production technology